2011
DOI: 10.1007/s00540-011-1168-6
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine and clonidine inhibit the function of NaV1.7 independent of α2-adrenoceptor in adrenal chromaffin cells

Abstract: Dexmedetomidine and clonidine inhibit the function of Na(v)1.7 independent of α(2)-adrenoceptor. These results may lead to a deeper understanding of the peripheral antinociceptive effects of α (2)-agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Moreover, it was reported that the α 2-adrenoceptor was expressed by more than 60% of neurons in the TG and over 80% of neurons in the DRG [ 5 , 6 ]. Recent studies demonstrate the antinociceptive mechanism of dexmedetomidine in the somatosensory system, specifically at the spinal cord and peripheral nervous system [ 8 , 19 , 20 , 25 ]. Several studies specifically targeted ion channels (VGSCs, hyperpolarization-activated cyclic nucleotide-gated channels) in the dorsal root ganglion that are primarily related to nociception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was reported that the α 2-adrenoceptor was expressed by more than 60% of neurons in the TG and over 80% of neurons in the DRG [ 5 , 6 ]. Recent studies demonstrate the antinociceptive mechanism of dexmedetomidine in the somatosensory system, specifically at the spinal cord and peripheral nervous system [ 8 , 19 , 20 , 25 ]. Several studies specifically targeted ion channels (VGSCs, hyperpolarization-activated cyclic nucleotide-gated channels) in the dorsal root ganglion that are primarily related to nociception.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies specifically targeted ion channels (VGSCs, hyperpolarization-activated cyclic nucleotide-gated channels) in the dorsal root ganglion that are primarily related to nociception. These studies show that the mechanism of action of dexmedetomidine is related to the suppression of these channels [ 8 , 19 , 20 , 26 ]. This suggests that dexmedetomidine blocks pain in the somatic system at the level of the peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking the I h current will result in prolonged hyperpolarization of the nerve, which seems to be more distinct in the unmyelinated C (i.e., pain) fibers than in α (i.e., motor) fibers. Furthermore, Maruta found that dexmedetomidine can inhibit the function of Na(v)1.7, independent of α-2-adrenoceptor in adrenal chromaffin cells [ 28 ]. This effect could not be prevented by a perfused α-2-receptor antagonist, which may imply the mechanism of the peripheral antinociceptive effects of α-2-agonists [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…But the newly performed studies have claimed that the peripheral and neuraxial effects of clonidine may have some different mechanism of action rather than the previously demonstrated role of clonidine as an alpha 2 adrenoceptor agonist. Though the exact mechanism is not clear, some hypothetical mechanisms have been proposed and a number of them like the role of clonidine in inhibition of tetrodotoxin-sensitive sodium channels have been demonstrated ( 10 ). Much more similar studies like the latter one are in process.…”
mentioning
confidence: 99%